Development of staircase-output multilevel inverter - Esfandiari, Ehsan (2011)
Due to several scenarios attached to the fossil fuel resources, the world has experienced a trend popularly towards alternative energy sources especially, renewable and clean in extraction as well as generation. This has raised the demand bar for the often popular solar and wind as the energy sources. As a result, renewable power conversion marketing has also dramatically increased during the past decade. Due to the application of inverters in power generation,the coinciding interest is shared equally and thus has created the basis of research interest on multi-level inverters. To acquire desired form of power, especially when precision, reliability and the economy of the project is considered upon, a multi-level inverter is a beneficial choice. They present ability to control higher amount of voltage and current, low THD, low cost, simple control methods, and compactness. Having exhibited its share of advantages in electronic power conversion, certain previous structures have indicated some limitations which risk hampering its fair deal of positive attributes. Such as the implementation of series connected switches (cascaded),a factor behind the inefficiency, operational heat generation and unreliability. A cascaded structure imposes two important limitations to the system: it limits the efficiency and reliability by increasing the on-state power dissipation in the converter; it directly limits the reliability by increasing the likelihood of failure. The selection of multi-level inverter configurations, on the basis of on-state voltage drop of switches is possible through developing a new mathematical method to calculate the comparative efficiency in staircase diode-clamped, H-bridge and the proposed inverter with pn junction and MOSFET switches. These calculations rely on the onstate voltage drop of p-n junction switches, conducting resistance of MOSFET switches, break down voltage, number of levels, peak output voltage, voltage steps magnitude and the load. The calculations show the important effect of on-state voltage drop of switches on the efficiency in staircase multi-level inverters. Using an affordable multi-winding transformer, a low frequency multi-level DC-AC-AC inverter is proposed and proves to be an advantageous choice. The most important advantage of this multilevel inverter is that only four switches conduct during each step,which means that it operates with lower number of serial conducting switches, resultantly increasing the efficiency and reliability. Higher reliability when switches fail in open-circuit and short-circuit behavior is another advantage of this inverter structure however, it is recommended to use switches that fail in open-circuit owning to higher reliability of the inverter in open-circuit failures. Furthermore, some important factors that affect the reliability of inverters have been improved in the proposed inverter, including:duty cycle of conducting switches, voltage stresses, switching frequency, switches temperature and dependency to capacitors. The system is controlled with a cheap microcontroller. A 5-kW 47-level prototype showed 97.4% ± 0.2% peak efficiency decreases to 91% under a full load and THD starts at 0.66% under a 50-W load increases to more than 7.5% under a full load. The novel proposed inverter, Switch-Ladder multi-level inverter, is a reliable and efficient choice for PV and renewable applications, where the output voltage peak is low and the volume and weight are not important parameters.